GLOBAL TRENDS IN ISLAMIC CHARACTER EDUCATION: A DECADE OF BIBLIOMETRIC ANALYSIS - Eko Ngabdul Shodikin; Shafira Azzahra; Luriana Rihadini (Proceeding of International Conference of Islamic Education, 2025)
This study investigates the global development of Islamic character education research using a bibliometric approach. The objective is to analyze publication trends, influential authors, journals, countries, and thematic directions between 2014 and 2025. The study adopts a quantitative bibliometric design to identify patterns and knowledge structures within the scope of Islamic character studies. Data were systematically collected from the Scopus database using the keyword “Islamic AND character” limited to English-language articles within the social sciences. A total of 200 eligible documents were selected through purposive sampling. The data were processed and analyzed using Biblioshiny and Bibliometrix tools to evaluate co-authorship networks, keyword co-occurrences, and citation impact. Results show a significant growth in publications after 2018, peaking in 2024. Indonesia emerged as the leading contributor, followed by the United States and Malaysia. Thematic analysis revealed that the dominant focus areas include Islamic education, moral development, and character formation in Islamic contexts. The most influential journals and authors predominantly come from Southeast Asia, indicating regional leadership in this field. The study concludes that bibliometric analysis offers valuable insights into the intellectual landscape of Islamic character education and highlights gaps in addressing contemporary issues such as digital ethics and global collaboration. These findings provide practical input for policy makers, curriculum developers, and future researchers to build data-driven strategies for character education rooted in Islamic values.